2013
DOI: 10.1016/j.molonc.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to paclitxel in breast carcinoma cells requires a quality control of mitochondrial antiapoptotic proteins by TRAP1

Abstract: Paclitaxel Apoptosis ER stress Drug resistance Breast carcinoma A B S T R A C TTRAP1 is a mitochondrial antiapoptotic protein up-regulated in several human malignancies. However, recent evidences suggest that TRAP1 is also localized in the endoplasmic reticulum (ER) where it is involved in ER stress protection and protein quality control of tumor cells. Based on the mechanistic link between ER stress, protection from apoptosis and drug resistance, we questioned whether these novel roles of TRAP1 are relevant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 40 publications
8
80
0
Order By: Relevance
“…Adaptation to ER stress conditions represents a mechanism of resistance to taxanes [8][9][10]; interestingly, our data show that paclitaxel induces apoptotic cell death and caspase 12 activation in MCF7 BC cells and enhances BiP/Grp78 and Grp94 expression [7]. Also in this context, a role of TRAP1 has been demonstrated by our groups: in fact, paclitaxel induces TRAP1 protein levels in MCF7 and MDA-MB231 BC cells, without affecting its mRNA expression.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…Adaptation to ER stress conditions represents a mechanism of resistance to taxanes [8][9][10]; interestingly, our data show that paclitaxel induces apoptotic cell death and caspase 12 activation in MCF7 BC cells and enhances BiP/Grp78 and Grp94 expression [7]. Also in this context, a role of TRAP1 has been demonstrated by our groups: in fact, paclitaxel induces TRAP1 protein levels in MCF7 and MDA-MB231 BC cells, without affecting its mRNA expression.…”
supporting
confidence: 73%
“…Using several inducible Myc cell models, as well as genetic and pharmacologic tools, Hart et al [26] have recently shown that Myc induction leads to activation of the PERK/eIF2α/ATF4 axis of the UPR, resulting in increased autophagy and protection against ER stress-dependent apoptosis. Similarly, we have demonstrated in CRC that increased TRAP1 expression correlates with increased expression of Myc, Grp78/BiP, ATF4 and increased phosphorylation of eIF2α [7,13,25].…”
Section: Trap1 Regulation Of Tumour Cell Metabolism Is Based On Attensupporting
confidence: 61%
See 3 more Smart Citations